Genome, biology and stability of the Thurquoise phage – A new virus from the Bastillevirinae subfamily - Węglewska, Martyna; Barylski, Jakub; Wojnarowski, Filip; Nowicki, Grzegorz; Łukaszewicz, Marcin (Frontiers in Microbiology, 2023)
Bacteriophages from the Bastillevirinae subfamily (Herelleviridae family) have proven to be effective against bacteria from the Bacillus genus including organisms from the B. cereus group, which cause food poisoning and persistent contamination of industrial installations. However, successful application of these phages in biocontrol depends on understanding of their biology and stability in different environments. In this study, we isolated a novel virus from garden soil in Wrocław (Poland) and named it ‘Thurquoise’. The genome of that phage was sequenced and assembled into a single continuous contig with 226 predicted protein-coding genes and 18 tRNAs. The cryo-electron microscopy revealed that Thurquoise has complex virion structure typical for the Bastillevirinae family. Confirmed hosts include selected bacteria from the Bacillus cereus group – specifically B. thuringiensis (isolation host) and B. mycoides, but susceptible strains display different efficiency of plating (EOP). The Latent and eclipse periods of Thurquoise in the isolation host last ~40 min and ~50 min, respectively. The phage remains viable for more than eight weeks in variants of the SM buffer with magnesium, calcium, caesium, manganese or potassium and can withstand numerous freeze-thaw cycles if protected by the addition of 15% glycerol or, to a lesser extent, 2% gelatine. Thus, with proper buffer formulation, this virus can be safely stored in common freezers and refrigerators for a considerable time. The Thurquoise phage is the exemplar of a new candidate species within the Caeruleovirus genus in the Bastillevirinae subfamily of the Herelleviridae family with a genome, morphology and biology typical for these taxa.